2016
DOI: 10.1073/pnas.1605554113
|View full text |Cite
|
Sign up to set email alerts
|

Online social integration is associated with reduced mortality risk

Abstract: Social interactions increasingly take place online. Friendships and other offline social ties have been repeatedly associated with human longevity, but online interactions might have different properties. Here, we reference 12 million social media profiles against California Department of Public Health vital records and use longitudinal statistical models to assess whether social media use is associated with longer life. The results show that receiving requests to connect as friends online is associated with r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
52
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(61 citation statements)
references
References 20 publications
(17 reference statements)
1
52
0
3
Order By: Relevance
“…With respect to health effects, it has consistently been shown that stronger social networks (either offline or online) are related to increased longevity 17 . As a biological correlate, social isolation (e.g., long-term unemployment, mental illness, homelessness, and displacement) are associated with higher fibrinogen levels, a marker for cardiovascular events 18 .…”
Section: Introductionmentioning
confidence: 99%
“…With respect to health effects, it has consistently been shown that stronger social networks (either offline or online) are related to increased longevity 17 . As a biological correlate, social isolation (e.g., long-term unemployment, mental illness, homelessness, and displacement) are associated with higher fibrinogen levels, a marker for cardiovascular events 18 .…”
Section: Introductionmentioning
confidence: 99%
“…We used data from the online social network Facebook to measure online social-network connectivity in the months and years before and after a loss. Past research has shown that online social interactions closely correspond to offline interactions [20][21][22] , as well as to important health outcomes such as subjective well-being 23 and longevity 24 . Although online interactions do not fully reflect social support provided offline, mundane chat is thought to play an important role in wellbeing 25 .…”
mentioning
confidence: 99%
“…Advances in these fields not only require conceptual and technical collaboration to devise treatable options [35] but could also involve ethical issues such as the ownership of data and providing access of genetic data to the participants, i.e., in other words, to answer the question Bwho owns the data [42]?B esides analysis of biological data, availability of other forms of data provides innovative methods to assess poverty and to understand how social interactions are related to health outcomes [43,44].…”
mentioning
confidence: 99%